2004
DOI: 10.2334/josnusd.46.221
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic perception and psychosocial impact of developmental enamel defects among Malaysian adolescents

Abstract: The aim of this study was to investigate the prevalence and psychosocial impact of enamel defects among 16-year-old school children on the island of Penang. The data were collected through a selfadministered questionnaire survey and an oral examination, using the Modified Developmental Defects of Enamel Index (FDI, 1992). In all, 1024 subjects were selected using a multistage random sampling technique. About two-thirds of the sample (67.1%) had at least one tooth affected by enamel defects. Enamel opacities ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
44
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 10 publications
4
44
1
Order By: Relevance
“…15,20 However, other studies have shown that higher levels of severity of the disease promoted a higher social and psychological discomfort. 21 The clinical characteristics of fluorosis lead to shy, sad, and quiet children who cover their faces with their hands to express happiness, smile with closed lips, do not participate in school social activities, and avoid talking with their classmates and smiling due to the shame of their dental appearance.…”
Section: Discussionmentioning
confidence: 98%
“…15,20 However, other studies have shown that higher levels of severity of the disease promoted a higher social and psychological discomfort. 21 The clinical characteristics of fluorosis lead to shy, sad, and quiet children who cover their faces with their hands to express happiness, smile with closed lips, do not participate in school social activities, and avoid talking with their classmates and smiling due to the shame of their dental appearance.…”
Section: Discussionmentioning
confidence: 98%
“…[23][24] There is a potential for hypoplasia to cause a negative impact because this type of enamel defect is more severe. In this study, hypoplasia was more prevalent among the children assessed, and this result may explain the association between DED and impacts on the functional limitation domain (Table 4), which is in agreement with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Both, Shah Alam and Seberang Prai have access to public water supply with fluoride level of 0.5 to 0.8 ppm since 1976. 11 Apart from water fluoridation, fluoride tooth paste is widely available in the markets of both areas. 12,13 Although, water fluoridation and fluoridated toothpaste are the 2 main strategies to prevent dental caries, there is still a need for school-based oral health education and preventive programs to promote good habits such as regular tooth brushing, flossing, and diet control.…”
Section: Introductionmentioning
confidence: 99%